Early neonatal hypoglycemia: incidence of and risk factors. A cohort study using universal point of care screening. (4th March 2019) - Bromiker, Ruben; Perry, Assaf; Kasirer, Yair; Einav, Sharon; Klinger, Gil; Levy-Khademi, Floris
Abstract: Objective: The objective of this study is to determine the true incidence of early neonatal hypoglycemia and to confirm potential risk factors. Study design: The study was conducted at tertiary Medical Center in Israel, between June and September 2014. First blood glucose concentrations of all infants admitted to the nursery were measured using a "point of care" analyzer (Accu-Chek). We recorded risk factors for hypoglycemia such as birth weight, gestational age, maternal diabetes and demographics and analyzed their association with two hypoglycemia cutoffs: 40 and 47 mg/dl. Results: Of 4000 newborns admitted during that period, 3595 were analyzed after excluding 405 who had missing data. Glucose level was obtained at a mean age of 74 ± 30 min. One hundred and twenty-four newborns (3.4%) had blood glucose levels below 40 mg/dl and 435 (12.1%) below 47 mg/dl. Univariate analyses revealed that gestational age, maternal diabetes, low birth weight (<2500 g), and twin delivery were associated with early neonatal hypoglycemia. Other risk factors (e.g. large or small for gestational age, birth weight >3800 g) were not. In multivariate analysis, gestational age remained the strongest association, while maternal diabetes and low birth weight became non-significant. Conclusions: We showed a high occurrence of early hypoglycemia in normal newborns using universal screening. The strongest risk factor was early gestational age. Surprisingly, incidence of early hypoglycemia in the presence of other classical risk factors was like that of the general population.